Post-Disaster Recovery Planning in Florida: A Resilient Solution to Counteract Reactive Federal Policy. - Frank, Adam. (2017)
Abstract: The opportunity to renew and rebuild after a disaster creates a potential to update and improve on previous infrastructure. This thesis will look at resiliency, the ability to withstand a devastating event by bending, but not breaking, as an ultimate goal for recovery planning. Current federal policy does not encourage recovery in a resilient way, an unintentional result of the five reactive federal recovery procedures and goals that now exist. How has the United States begun to counteract these reactive tendencies? Florida has created a framework document for preparing a Post-Disaster Redevelopment Plan (PDRP) and has mandated PDRP development in all coastal communities. The key to the PDRP is to detail possible advancement strategies in land use, housing, infrastructure, economic development, environmental protection and public participation to facilitate proactive community standards for rebuilding in the wake of a major event. By comparing the PDRP components with the reactive policies that are addressed, the state of Florida provides an example depicting how proactive planning can address problems that reactive planning cannot.; Thesis (M.A.)--Tufts University, 2011.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Rusty Russell.; Committee: Ann Rappaport.; Keyword: Urban planning.